A carbon-based metal single atom catalyst and its preparation method and its application in catalytic carbon dioxide hydrogenation to methanol
The carbon-based metal single-atom catalyst is prepared in one step by DC arc discharge method, which solves the problems of complex preparation of single-atom catalysts in the prior art and poor thermal stability, and realizes a catalyst that remains stable at high temperatures, and exhibits low starting temperature and high methanol selectivity when catalyzing carbon dioxide hydrogenation to methanol.
Patent Information
- Application Number
- CN202411694364.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-11-25
AI Technical Summary
The existing single-atom catalyst preparation methods have problems such as cumbersome steps, low yield and poor thermal stability, which limits its practical application in the catalytic field. At the same time, the existing catalysts lack thermal stability and methanol selectivity when catalyzing carbon dioxide hydrogenation to methanol.
The carbon-based metal single atom catalyst was prepared in one step by direct current arc discharge method. The catalyst prepared was maintained stable at high temperatures by using a graphene support and the metal single atom embedded therein and was used to catalyze the hydrogenation of carbon dioxide to produce methanol.
A simple and efficient carbon-based metal single-atom catalyst is achieved. The catalyst maintains a single-atom state below 500 °C, has excellent thermal stability, and the catalytic activation temperature is low when catalyzed in the production of methanol by catalytic reduction of carbon dioxide, and the methanol selectivity can reach 100%.
Smart Images

Figure CN119186563B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of single-atom material preparation and catalyst technology, and in particular to a carbon-based metal single-atom catalyst and a preparation method thereof, and application thereof in catalyzing carbon dioxide hydrogenation to produce methanol. Background Art
[0002] Single-atom materials have attracted much attention in the field of catalysis due to their 100% atomic utilization and low coordination environment. Single-atom materials can provide higher reaction activation energy and are ideal catalysts for most reactions. However, the synthetic methods commonly used to prepare single-atom catalysts, such as chemical modification, impregnation, and atomic layer deposition, all have problems such as cumbersome steps, low yield, and lack of universality; and the prepared single-atom materials have problems such as poor thermal stability, easy sintering and deactivation at high temperature, and complex preparation. Therefore, the practical application of single-atom materials in the field of catalysis is limited.
[0003] In addition, catalytic conversion of carbon dioxide into high-value-added chemical raw materials is an ideal way to effectively alleviate the energy crisis and greenhouse effect. Methanol, as one of the important chemical raw materials, can be used to synthesize a series of industrial chemicals such as low-carbon olefins and petroleum. Therefore, researchers have long been committed to how to efficiently hydrogenate carbon dioxide into methanol. The key to the conversion rate of catalytic reduction of carbon dioxide to methanol lies in the catalyst. Currently, Cu-ZnO-Al2O3 catalysts are commonly used in industry. This type of catalyst has defects such as poor thermal stability, easy sintering and deactivation at high temperature, and low methanol selectivity.
[0004] Based on this, there is an urgent need for a single-atom catalyst that is simple to prepare and can maintain good stability at high temperatures, so as to promote the practical application of single-atom materials in catalytic fields such as catalytic reduction of carbon dioxide. Summary of the invention
[0005] To solve the above problems, the present invention provides a carbon-based metal single atom catalyst and a preparation method thereof and an application thereof in catalytic hydrogenation of carbon dioxide to methanol. The carbon-based metal single atom catalyst comprises a graphene carrier and metal single atoms embedded in the vacancies of the graphene carrier, and can be prepared in one step from a carbon source and a metal source by a direct current arc discharge method. The preparation method is simple and efficient, and the single atoms in the prepared carbon-based metal single atom catalyst can still remain stable at 500°C. Among them, the carbon-based copper single atom catalyst can be used as a catalyst in the catalytic reduction of carbon dioxide to methanol, which not only has a low catalytic activation temperature, but also has a selectivity of up to 100% for the product methanol.
[0006] Specifically, the present invention provides the following technical solutions:
[0007] The first aspect of the present invention provides a method for preparing a carbon-based metal single-atom catalyst, comprising:
[0008] Filling a mixed powder of a metal source and a carbon source uniformly into a hollow graphite rod to obtain a graphite rod containing a metal source;
[0009] A graphite rod containing a metal source is used as an anode of a DC arc discharge cavity, a pure graphite rod is used as a cathode of the DC arc discharge cavity, and DC arc discharge is performed in the presence of a protective gas to form the composite catalyst on the DC arc discharge cavity;
[0010] The carbon-based metal single atom catalyst comprises a graphene support and metal single atoms, wherein the metal single atoms are embedded in carbon vacancies of the graphene support.
[0011] Furthermore, the metal source is preferably one or more of copper powder, copper oxide powder, indium oxide powder, and titanium oxide powder, but is not limited to the types of metal sources listed above.
[0012] Furthermore, the carbon source is preferably one or more of amorphous carbon, graphite powder, and activated carbon.
[0013] Furthermore, the molar ratio of the metal element to the carbon element in the mixed powder is 1:(1-100), for example 1:1, 1:5, 1:15, 1:25, 1:35, 1:45, 1:55, 1:65, 1:75, 1:85, 1:95, 1:100, etc., including but not limited to the ratios listed above.
[0014] Furthermore, the ratio of the diameter to the inner diameter of the hollow graphite rod is 1:(0.05-1), such as 1:0.1, 1:0.2, 1:0.3, 1:0.5, 1:0.75, 1:0.8, etc., wherein the inner diameter is the equivalent diameter of the hollow cavity of the hollow graphite rod.
[0015] Furthermore, the diameter of the graphite rod containing the metal source is the same as that of the pure graphite rod.
[0016] Furthermore, the spacing between the anode and the cathode is 1-10 mm, for example, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, 10 mm, etc., including but not limited to the values listed above.
[0017] Furthermore, the graphite rod containing the metal source has the same length as the pure graphite rod, and the two ends of the cathode and the anode in the DC arc discharge chamber are horizontally opposite to each other, thereby ensuring that the graphite rod can be consumed stably and evenly.
[0018] Furthermore, the protective gas is selected from one or more of argon, helium, neon, krypton, radon and nitrogen.
[0019] Furthermore, the preparation method also includes first evacuating the DC arc discharge cavity to a pressure less than 10 Pa, and then introducing a protective gas; after the protective gas is introduced, the pressure of the DC arc discharge cavity is 20-500 Torr.
[0020] Furthermore, the discharge current of the DC arc discharge is preferably 5-200 A, for example, 5 A, 20 A, 40 A, 60A, 80 A, 100 A, 120 A, 140 A, 160 A, 180 A, 200 A, etc., including but not limited to the current values listed above; the voltage of the DC arc discharge is 5-200 V, for example, 5 V, 20 V, 40 V, 60 V, 80 V, 100 V, 120 V, 140V, 160 V, 180 V, 200 V, etc., including but not limited to the voltage values listed above.
[0021] The second aspect of the present invention provides a carbon-based metal single-atom catalyst prepared by the preparation method described in the first aspect. The metal single atom in the carbon-based metal single-atom catalyst prepared by the above method has excellent thermal stability.
[0022] Furthermore, the metal is preferably one or more of copper, indium and titanium.
[0023] Furthermore, the metal single atom in the carbon-based metal single atom catalyst can maintain a single atom state below 500°C.
[0024] The third aspect of the present invention provides an application of the carbon-based metal single-atom catalyst described in the second aspect in catalytic reduction of carbon dioxide to produce methanol, wherein the metal single atom in the carbon-based metal single-atom catalyst is a copper single atom and / or a titanium single atom.
[0025] Furthermore, when the metal single atom in the carbon-based metal single atom catalyst is a copper single atom, in the preparation method of the carbon-based metal single atom catalyst, the molar ratio of copper element to carbon element in the mixed powder is preferably (1-8):15, for example, 1:15, 2:15, 3:15, 4:15, 5:15, 6:15, 7:15, 8:15, etc. The molar ratio of copper to carbon in the mixed powder will affect the conversion rate of carbon dioxide and the selectivity of product methanol in the process of catalytic reduction of carbon dioxide hydrogenation by the catalyst as a catalyst. Too low or too high copper content will reduce the conversion rate of carbon dioxide, and the selectivity of product methanol decreases with the increase of copper content. Based on this, in order to obtain a catalyst with both high conversion rate and high selectivity for product methanol, the molar ratio of copper element to carbon element in the mixed powder needs to be controlled in the range of (1-8):15, more preferably in the range of (1-2.5):15.
[0026] Furthermore, when the metal single atom in the carbon-based metal single atom catalyst is a copper single atom, in the preparation method of the carbon-based metal single atom catalyst, the discharge current of the DC arc discharge is preferably 80-130 A, for example, 80 A, 90 A, 100 A, 110 A, 120 A, 130 A, etc., including but not limited to the current values listed above; more preferably 110 A.
[0027] Furthermore, the carbon-based metal single-atom catalyst is filled into a reaction tube, a mixed gas of carbon dioxide and hydrogen is introduced, and a catalytic reaction is carried out under pressure; the volume ratio of carbon dioxide to hydrogen in the mixed gas is 1:3, the pressure is 2.5 MPa, and the space velocity of the mixed gas is 2400-2800 mL / (g·h); when the metal single atom in the carbon-based metal single-atom catalyst is a copper single atom, the temperature of the catalytic reaction is 180-300°C, more preferably 180-240°C, and the selectivity of the product methanol is 100%.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] 1. The present invention provides a method for preparing a carbon-based metal single-atom catalyst, which is prepared in one step from a carbon source and a metal source by a direct current arc discharge method. The preparation method is simple, efficient and low-cost, and can stably synthesize a carbon-based metal single-atom catalyst with high thermal stability, which is suitable for mass production.
[0030] 2. The carbon-based metal single atom catalyst prepared by the above method comprises a graphene carrier and metal single atoms embedded in the carbon vacancies of the graphene carrier. The metal single atoms in the catalyst can maintain a stable single atom state within 20-500°C, showing extremely high thermal stability.
[0031] 3. The carbon-based copper single-atom catalyst provided by the present invention can be used as a catalyst for catalytic reduction of carbon dioxide to produce methanol. The catalyst can not only be activated at low temperature (180°C) to activate carbon dioxide and hydrogen to produce methanol, but also the selectivity of the methanol of the catalytic product can reach 100% at a catalytic temperature of 180-240°C; in addition, the catalyst exhibits long-term stability, and the catalytic activity does not change significantly after continuous catalytic reduction of carbon dioxide for 100 hours. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is a high-angle dark-field spherical aberration electron microscopy image of the carbon-based copper single-atom catalyst prepared in Example 1 of the present invention, with a scale of 2 nm;
[0033] Figure 2 This is a Raman spectrum of the carbon-based copper single-atom catalyst prepared in Example 1 of the present invention;
[0034] Figure 3 This is the XPS C1s spectrum of the carbon-based copper single-atom catalyst prepared in Example 1 of the present invention;
[0035] Figure 4 This is a high-angle dark-field spherical aberration electron microscopy image of the carbon-based copper single-atom catalyst prepared in Example 1 of the present invention after being kept at 300°C for 100 hours, with a scale of 1 nm;
[0036] Figure 5 This is a high-angle dark-field spherical aberration electron microscopy image of the carbon-based copper single-atom catalyst prepared in Example 1 of the present invention after being kept at 500°C for 100 hours, with a scale of 2 nm;
[0037] Figure 6 The carbon-based copper single-atom catalyst prepared in Example 1 of the present invention is used to catalyze the reduction of carbon dioxide to produce methanol at different temperatures and to measure the methanol selectivity and carbon dioxide conversion rate;
[0038] Figure 7 This is a curve diagram of the change in conversion frequency of the carbon-based copper single-atom catalyst prepared in Example 1 of the present invention during the catalytic reduction of carbon dioxide at 240°C for 100 hours. DETAILED DESCRIPTION
[0039] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the present invention belongs. The terms used herein in the specification of the present invention are for the purpose of describing specific embodiments only and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items. The "include" or "comprising" described in the present invention means that in addition to the components described, other components may also be included or contained. The "include" or "comprising" described in the present invention may also be replaced by the closed "for" or "consisting of...".
[0040] The present invention is further described below in conjunction with specific embodiments and drawings so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention. Example 1
[0041] This embodiment relates to the preparation of a carbon-based copper single-atom catalyst, which is specifically as follows:
[0042] Graphite powder (purity 99%) and copper oxide powder (purity 99.99%) were uniformly mixed at a Cu:C molar ratio of 2:15 and filled into a hollow graphite rod with a diameter of 8 mm (inner diameter 6 mm). One end of the copper-containing graphite rod was fixed on the DC arc chamber as the anode, and one end of another pure graphite rod with a diameter of 8 mm was fixed on the cathode of the DC arc chamber, keeping the ends of the graphite rods of the cathode and cathode horizontally opposite to each other, and keeping the distance between the cathode and cathode ends at about 10 mm.
[0043] The DC discharge chamber was evacuated to a pressure of less than 10 Pa, and high-purity helium was introduced to 200 Torr. The electric welder was turned on, the current was maintained at 110 A, and arc discharge began. During the discharge process, the anode was continuously consumed until the anode graphite rod was completely consumed, and the discharge was stopped. The discharge process lasted about 5 minutes. The black powder generated on the inner wall of the DC discharge chamber was the catalyst powder.
[0044] The spherical aberration electron microscope image of the catalyst prepared in this example is as follows Figure 1 As shown, the brighter atoms in the figure are heavier metal copper atoms, and the darker parts are graphene. It can be concluded that copper is dispersed in the graphene in the form of single atoms.
[0045] The Raman spectrum of the composite catalyst prepared in this example ( Figure 2 ) also shows the G peak and D peak characteristics of carbon (ID / IG = 0.74), which are related to graphitized sp2 carbon and disordered carbon or defective carbon, respectively, proving the existence of graphene structure in the catalyst.
[0046] The XPS C1s spectrum of the catalyst is shown in Figure 3 As shown in the figure, the narrow scan of the C1s peak is decomposed into five characteristic peaks, corresponding to C=C, CC, CO, OC=O and π-π* vibrational transitions, with binding energies of 284.0 eV, 284.4 eV, 286.2 eV, 287.6 eV and 290.7 eV, respectively. In particular, the π-π* vibrational transition is obtained at 290.7 eV, indicating that there is an electronic interaction between Cu atoms and defective graphene.
[0047] In summary, the catalyst prepared in this embodiment includes graphene and single-atom copper embedded in the carbon vacancies of graphene.
[0048] Thermal stability test:
[0049] The carbon-based copper single-atom catalyst prepared in this example was placed in an inert gas flow at 300°C and 500°C for 100 h, and then the samples were taken out and observed under an electron microscope. The results are as follows: Figure 4 , Figure 5As shown, after being kept at 300°C and 500°C for 100 h, the single-atom copper in the sample still exists stably in the graphene. It can be seen that the single-atom copper in the carbon-based copper single-atom catalyst prepared in this example has extremely high thermal stability. Example 2
[0050] This embodiment relates to the preparation of a carbon-based copper single-atom catalyst, and the only difference from Example 1 is that graphite powder (purity 99%) and copper oxide powder (purity 99.99%) are uniformly mixed at a Cu:C molar ratio of 1:15; the remaining operations are the same to prepare a composite catalyst powder. Example 3
[0051] This embodiment relates to the preparation of a carbon-based copper single-atom catalyst, and the only difference from Example 1 is that graphite powder (purity 99%) and copper oxide powder (purity 99.99%) are uniformly mixed at a Cu:C molar ratio of 3:15; the remaining operations are the same to prepare a composite catalyst powder. Example 4
[0052] This embodiment relates to the preparation of a carbon-based copper single-atom catalyst, and the only difference from Example 1 is that graphite powder (purity 99%) and copper oxide powder (purity 99.99%) are uniformly mixed at a Cu:C molar ratio of 4:15; the remaining operations are the same to prepare a composite catalyst powder. Example 5
[0053] This embodiment relates to the preparation of a carbon-based copper single-atom catalyst, and the only difference from Example 1 is that graphite powder (purity 99%) and copper oxide powder (purity 99.99%) are uniformly mixed at a Cu:C molar ratio of 8:15; the remaining operations are the same to prepare a composite catalyst powder. Example 6
[0054] This embodiment relates to the preparation of a carbon-based indium single-atom catalyst, and the only difference from Example 1 is that the copper oxide powder is replaced with an equimolar amount of indium oxide, and the other operations are the same to prepare a carbon-based indium single-atom catalyst. Example 7
[0055] This embodiment relates to the preparation of a carbon-based titanium single-atom catalyst, and the only difference from Example 1 is that the copper oxide powder is replaced with an equimolar amount of titanium oxide, and the other operations are the same to prepare a carbon-based titanium single-atom catalyst. Comparative Example 1
[0056] This comparative example involves the preparation of a catalyst, and the only difference from Example 1 is that graphite powder (purity 99%) is filled in a hollow graphite rod with a diameter of 8 mm; the other operations are the same, and catalyst powder is prepared. Comparative Example 2
[0057] In this comparative example, graphene-supported copper nanoparticles were synthesized according to a method reported in the literature (Angew. Chem. Int. Ed. 2015, 54, 2100–2104). The preparation method comprises the following steps:
[0058] 40 mL Cu(NO3)2(1.2 mol / L), Na4EDTA(0.6 mol / L) aqueous solution and 20 mL ethanol were mixed and added to a 100 mL reactor at 200 ℃ for 24 h. After cooling to room temperature, the solid was filtered, washed, and dried at 100 ℃ to obtain EDTA-Cu. The obtained solid was placed in a tube furnace, heated to 600 ℃ at a rate of 10 ℃ / min under argon atmosphere, calcined at constant temperature for 3 h, and then cooled naturally. The sample was placed in a 0.5 M sulfuric acid solution, heated and stirred in an oil bath at 90 ℃ for 4 h, and finally filtered, washed, and dried to obtain graphite-wrapped Cu nanoparticles (CuNPs / G).
[0059] Thermal stability test: The composite catalyst prepared in this comparative example was placed in an inert gas flow at 500°C for 100 h, and then the sample was taken out and observed under an electron microscope. The results showed that the copper nanoparticles sintered and agglomerated on the graphene surface.
[0060] Application and performance testing
[0061] (1) Taking the carbon-based copper single atom catalyst prepared in Example 1 as an example, the methanol selectivity and carbon dioxide conversion rate in the catalytic reduction of carbon dioxide to methanol at different temperatures were studied. The specific operation was as follows:
[0062] The catalyst performance evaluation was carried out on a fixed-bed continuous flow reactor-GC-MS / MS chromatography. The carbon-based copper single-atom catalyst prepared in Example 1 was crushed and sieved, and then 500 mg of the catalyst was filled into a reaction tube. The reaction was carried out at 2.5 MPa and different temperatures (180°C, 200°C, 220°C, 240°C, 260°C, 280°C, and 300°C). A mixed gas of carbon dioxide and hydrogen in a volume ratio of 1:3 was used as the reaction gas, and the volume space velocity was 2400 mL / (g·h).
[0063] Test results such as Figure 6 As shown in the figure, within the test temperature range, the conversion rate of carbon dioxide increases with the increase of temperature. Within the reaction temperature of 180-240 ℃, the selectivity of the reaction product methanol can reach 100%. When the temperature is greater than 240 ℃, the selectivity of the product methanol decreases with the increase of temperature.
[0064] (2) The methanol selectivity and carbon dioxide conversion rate of the materials prepared in the above examples and comparative examples as catalysts in the catalytic reduction of carbon dioxide to methanol were studied as follows:
[0065] The catalyst performance evaluation was carried out on a fixed-bed continuous flow reactor-GC-MS / MS chromatography, using a commercially available industrial copper-zinc-aluminum catalyst CuO-ZnO-Al2O3 as a control sample. The materials prepared in the above Examples 1-7, Comparative Example 1, and Comparative Example 2 and the control sample were crushed and sieved, and 500 mg of the catalyst was filled into a reaction tube respectively. The reaction was carried out at 2.5 MPa and 240°C, and a mixed gas of carbon dioxide and hydrogen in a volume ratio of 1:3 was used as the reaction gas, and the volume space velocity was 2400 mL / (g·h).
[0066] The test results are shown in Table 1 below:
[0067] Table 1
[0068]
[0069] As can be seen from Table 1, the carbon-based metal single-atom catalysts prepared in Examples 1-7 can all be used as catalysts to catalytically reduce carbon dioxide to produce methanol, and the carbon-based copper atom catalysts prepared in Examples 1-5 all show high selectivity in the catalytic reduction of carbon dioxide to produce methanol, wherein the selectivity of the reduction product methanol in Examples 1 and 2 is as high as 100%. Under the same conditions, the industrial copper-zinc-aluminum catalyst (control sample) has a relatively high carbon dioxide conversion rate, but 89.6% of the reduction product of carbon dioxide is carbon monoxide, and only 10.4% is the target product methanol. In the same time, the methanol obtained by treating carbon dioxide is lower than that of the catalyst prepared in Examples 1-4, and the large amount of by-products produced increases the processing cost.
[0070] It can be seen from Examples 1, 6, and 7 that changing the metal source will affect the catalytic activity of the composite catalyst and the selectivity to the product. For example, Example 6 and Example 1 adopt the same method to prepare graphene-loaded catalysts with different metals. Among them, the carbon-based indium single-atom catalyst (Example 6) has a much lower catalytic activity for carbon dioxide than the carbon-based copper single-atom catalyst prepared in Example 1 under the same catalytic conditions, and the selectivity of the carbon-based indium single-atom catalyst for the product methanol is low, at 38.2%.
[0071] In addition, the catalyst prepared without adding a copper source in Comparative Example 1 and the composite catalyst of graphene-loaded copper nanoparticles prepared in Comparative Example 2 were both unable to catalyze the reduction of carbon dioxide at 240°C. It can be seen that the introduction of single-atom copper can effectively reduce the activation temperature of the catalyst, so that the composite catalyst prepared by the present invention can activate carbon dioxide and hydrogen at 180°C and can still maintain activity at a high temperature of 300°C.
[0072] (3) Taking the carbon-based copper single atom catalyst prepared in Example 1 as an example, the stability of the carbon-based copper single atom catalyst as a catalyst in the application of catalytic reduction of carbon dioxide to methanol was studied.
[0073] The carbon-based copper single atom catalyst prepared in Example 1 was used as a catalyst to continuously catalyze the reduction of carbon dioxide at 240 °C for 100 h. Figure 7 As shown, the catalyst was used for continuous catalytic reduction of carbon dioxide for 100 h without significant change in catalytic activity, demonstrating excellent long-term catalytic stability.
[0074] In summary, the carbon-based metal single-atom catalyst provided by the present invention has excellent thermal stability. Among them, the carbon-based copper single-atom catalyst in the catalytic reduction of carbon dioxide to produce methanol not only has a low activation temperature, excellent thermal stability and long-term catalytic stability, but also has high selectivity for the product methanol in a large temperature range, which can reach 100%.
[0075] The above-described embodiments are only preferred embodiments for fully illustrating the present invention, and the protection scope of the present invention is not limited thereto. Equivalent substitutions or changes made by those skilled in the art based on the present invention are within the protection scope of the present invention. The protection scope of the present invention shall be subject to the claims.
Claims
1. Application of a carbon-based metal single atom catalyst in catalytic reduction of carbon dioxide to methanol, characterized in that: The metal single atom in the carbon-based metal single atom catalyst is a copper single atom and / or a titanium single atom; The preparation method of the carbon-based metal single-atom catalyst comprises: Filling a mixed powder of a metal source and a carbon source uniformly into a hollow graphite rod to obtain a graphite rod containing a metal source; A graphite rod containing a metal source is used as an anode of a DC arc discharge cavity, a pure graphite rod is used as a cathode of the DC arc discharge cavity, and DC arc discharge is performed in the presence of a protective gas to form the carbon-based metal single atom catalyst in the DC arc discharge cavity; The carbon-based metal single atom catalyst comprises a graphene support and metal single atoms, wherein the metal single atoms are embedded in carbon vacancies of the graphene support.
2. The use according to claim 1, characterized in that: The metal source is selected from one or more of copper powder, copper oxide powder, and titanium oxide powder; The carbon source is selected from one or more of amorphous carbon, graphite powder and activated carbon.
3. The use according to claim 1, characterized in that: The molar ratio of the metal element to the carbon element in the mixed powder is 1:(1-100).
4. The use according to claim 1, characterized in that: The ratio of the diameter to the inner diameter of the hollow graphite rod is 1:(0.05-1); The diameter of the graphite rod containing the metal source is the same as that of the pure graphite rod.
5. The use according to claim 1, characterized in that: The distance between the anode and the cathode is 1-10 mm; The graphite rod containing the metal source has the same length as the pure graphite rod, and the two ends of the cathode and the anode in the DC arc discharge chamber are horizontally opposite to each other.
6. The use according to claim 1, characterized in that: The protective gas is selected from one or more of argon, helium, neon, krypton, radon and nitrogen; The preparation method also includes first evacuating the DC arc discharge cavity to a pressure less than 10 Pa, and then introducing a protective gas; after the protective gas is introduced, the pressure of the DC arc discharge cavity is 20-500 Torr.
7. The use according to claim 1, characterized in that: The discharge current of the DC arc discharge is 5-200 A, and the voltage is 5-200 V.